2012
DOI: 10.1074/mcp.m112.017988
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Identification of Annexin A2 as a Key Mediator in the Metastasis and Proangiogenesis of Endometrial Cells in Human Adenomyosis

Abstract: Adenomyosis is a common estrogen-dependent disorder of females characterized by a downward extension of the endometrium into the uterine myometrium and neovascularization in ectopic lesions. It accounts for chronic pelvic pain, dysmenorrhea, menorrhagia, and infertility in 8.8 -61.5% women worldwide. However, the molecular mechanisms for adenomyosis development remain poorly elucidated. Here, we utilized a two-dimensional polyacrylamide gel electrophoresis/MS-based proteomics analysis to compare and identify d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 45 publications
4
88
0
1
Order By: Relevance
“…In AM, the invasion and metastastic abilities of endometrial cells are enhanced, which is an important cause of the disease (29). To the best of our knowledge, the present study was the first to investigate whether miR-17 is involved in altering the biological functions of endometrial cells.…”
Section: Discussionmentioning
confidence: 87%
“…In AM, the invasion and metastastic abilities of endometrial cells are enhanced, which is an important cause of the disease (29). To the best of our knowledge, the present study was the first to investigate whether miR-17 is involved in altering the biological functions of endometrial cells.…”
Section: Discussionmentioning
confidence: 87%
“…The mechanisms of E-cadherin loss in malignant cancers include genetic mutation, epigenetic silencing, transcription repression and proteolytic processes (4). Another research group has also demonstrated that upregulation of ANXA2 is accompanied by the EMT process in endometrial cells, and forced expression of ANXA2 may mediate phenotypic mesenchymal-like cellular changes with structural and functional alteration in a β-catenin/TCF signal-associated manner (29). This could be reversed by inhibition of ANXA2 expression, and another study suggested that ANXA2 is closely associated with tumor progression in HeLa cells (30).…”
mentioning
confidence: 89%
“…The estrogen dependency is often accompanied by the appearance of EMT features, which is a crucial step for the acquisition of invasive properties of endometrial epithelial cells during adenomyosis progression (22). Estrogen enhances endometrial tissue growth, metastasis and angiogenesis in an adenomyosis model via annexin A2 (ANXA2)-induced EMT (23). These data implicate the crucial role of estrogen-induced EMT in the development of adenomyosis (22).…”
Section: Epithelial-mesenchymal Transition Theorymentioning
confidence: 72%